Impact of pulsatile perfusion on postoperative outcome of kidneys from controlled donors after cardiac death. - Plata-Munoz, J; Muthusamy, A; Quiroga, I; Contractor, H; Sinha, S; Vaidya, A; Darby, C; Fuggle, S; Friend, P (2008)
Pulsatile perfusion (PP) might be a cost-effective cold preservation technique to reduce the incidence of delayed graft function (DGF) in kidneys from deceased donors. With the aim to address whether PP can reduce the incidence of DGF in kidneys from controlled donors after cardiac death (cDCD), we compared the clinical outcome of 30 recipients of kidneys from cDCD preserved by static cold storage (cDCD-SCS) with 30 recipients of cDCD kidneys preserved by PP (cDCD-PP). The end-points were the incidence of primary nonfunction (PNF), DGF and acute rejection (AR), the length of hospitalization, 1, 3, 6 and 12-months graft function, graft survival and patient survival. Donor, recipient and preimplantation data were well matched. DGF was significantly lower (53.3% vs. 86.6% P<0.001) and the length of hospitalization shorter (10 vs. 14 days P<0.033) in the cDCD-PP group. Similarly, postoperative and short-term graft function (7 and 30 days and 6 and 12 months, respectively) was statistically better in the cDCD-PP than in the cDCD-SCS. In summary, in this cohort, clinical introduction of PP was associated with a significant reduction of DGF, shorter hospitalization and better graft function than SCS.